KAJIAN IKONOGRAFI KARYA DULLAH â€œPRAKTIK TENTARA PENDUDUKAN ASINGâ€ - Adisukma, Wisnu (Institut Seni Indoensia Surakarta, 2016)
The article with the title Iconography Study of Work Dullah â€œArmy Practice of Foreign Occupationâ€œÂ intended to seek the textual and contextual meaning of painters Dullah. With the approach ofÂ iconography will be obtained meaning that deeper and broader than a work of art. Through thisÂ approach, the artwork will be a major concern in reviewing the history of art, nevertheless alsonecessary to understand the contextual and symbolic aspects. At the time of independence, DullahÂ many immortalize the events related to the struggle of Indonesian nation in seizing and maintainingÂ independence in his works. Dullah even led a group of young artists to paint directly events duringthe occupation of Yogyakarta as an effort documenting the history of the national struggle. One ofÂ his very powerful is the â€œArmy Practice of Foreign Occupationâ€œ that depicts cruelty colonizers againstÂ the indigenous population. In this case the work Dullah Practice Foreign Occupation Army will findits context as understood by tracing the history of socio-cultural-years 1940-1950an. From the workÂ we can find out how the socio-historical situation of the community when the colonial era.Keywords: Dullah, Iconography, Army Practice of Foreign Occupation.